Endoplasmic Reticulum-Mitochondria Contacts: A Potential Therapy Target for Cardiovascular Remodeling-Associated Diseases - Wang, Yu; Zhang, Xinrong; Wen, Ya; Li, Sixuan; Lu, Xiaohui; Xu, Ran; Li, Chao (Frontiers in Cell and Developmental Biology, 2021)
Cardiovascular remodeling occurs in cardiomyocytes, collagen meshes, and vascular beds in the progress of cardiac insufficiency caused by a variety of cardiac diseases such as chronic ischemic heart disease, chronic overload heart disease, myocarditis, and myocardial infarction. The morphological changes that occur as a result of remodeling are the critical pathological basis for the occurrence and development of serious diseases and also determine morbidity and mortality. Therefore, the inhibition of remodeling is an important approach to prevent and treat heart failure and other related diseases. The endoplasmic reticulum (ER) and mitochondria are tightly linked by ER-mitochondria contacts (ERMCs). ERMCs play a vital role in different signaling pathways and provide a satisfactory structural platform for the ER and mitochondria to interact and maintain the normal function of cells, mainly by involving various cellular life processes such as lipid metabolism, calcium homeostasis, mitochondrial function, ER stress, and autophagy. Studies have shown that abnormal ERMCs may promote the occurrence and development of remodeling and participate in the formation of a variety of cardiovascular remodeling-associated diseases. This review focuses on the structure and function of the ERMCs, and the potential mechanism of ERMCs involved in cardiovascular remodeling, indicating that ERMCs may be a potential target for new therapeutic strategies against cardiovascular remodeling-induced diseases.